VMI for single-vendor multi-retailer supply chains under stochastic demand. (January 2015) - Mateen, Arqum; Chatterjee, Ashis Kumar; Mitra, Subrata
Highlights: We present an approximate expression for the expected total cost of a single vendor – multiple retailer VMI system. Validity of the expression has been tested through simulation. Levers for controlling and monitoring the system have been analyzed. Abstract: This paper discusses how a vendor and multiple retailers interact in a vendor managed inventory (VMI) system under stochastic demand. It is assumed that the vendor replenishes all the retailers at the same time. The vendor replenishment cycle is taken to be an integer multiple of the retailer replenishment cycle. In case of a shortage at the vendor, the available stock is allocated to the retailers on the basis of equal stock out probability. Approximate expressions for minimizing the expected total cost for the VMI system have been developed. Various levers affecting the performance of the system have been analyzed. The validity of the approximate model has been tested through simulation.